A conceptual model of woodland use and change in Zimbabwe - Campbell, Bruce M.; Frost, P.; Goebel, A.; Standa-Gunda, W.; Mukamuri, B.; Veenan, M. (2000)
This paper use a conceptual box-and-arrow model for understanding woodland use in Zimbabwe in the context of the complex ecological-social-economic system of which it is part. Central themes within the model are: the policy framework; local institutions; land pressures; rural-urban relationships; the rise in tourism; increasing commercialisation of woodland products; drought; AIDS; and the status of the resource itself. It is suggested that too little attention has been paid to the impacts of policy on woodland use and commercialisation, and that woodland use is seldom seen in the wider context of the entire household livelihood system. Conceptual models represent a tool for understanding the connections between the components of complex systems, but they need to be followed by more detailed simulation modelling, to understand both the dynamics of these systems and the possible outcomes of various interventions in them.